Wolf Media Coverage in the Region of Castilla y León (Spain): Variations over Time and in Two Contrasting Socio-Ecological Settings - Miguel Delibes-Mateos (Animals, 2020)
People’s attitudes towards large carnivores, and thus public support for their conservation, can be influenced by how these species are framed in the media. Therefore, assessing media coverage of large carnivores is of particular interest for their coexistence with humans. I used content analysis to assess how the grey wolf was portrayed in a newspaper in northern Spain, how wolf media coverage varied over time (2006–2017), and in two different socio-ecological settings. Most documents addressed the conflictive relationship between the wolf and livestock (60%; n = 902). Moreover, coverage of this relationship increased over the study period in the south of the study area, where the wolf is strictly protected, has recolonised new localities, and damage to livestock has increased. Overall, other topics, such as wolf conservation or hunting, appeared much less frequently in the media, but predominated in the north of the study area, where the wolf is more abundant and huntable. Conflictive issues like wolf-livestock interactions are generally attractive for audiences, but drawing attention to this issue may compromise the management of conflicts associated with wolves. Ideally, the media should promote potential wolf conservation values if coexistence between wolves and humans is sought.